Metagenomics Investigation of Agarlytic Genes and Genomes in Mangrove Sediments in China: A Potential Repertory for Carbohydrate-Active Enzymes - Qu, Wu; Lin, Dan; Zhang, Zhouhao; Di, Wenjie; Gao, Boliang; Zeng, Runying (Frontiers in Microbiology, 2018)
Monosaccharides and oligosaccharides produced by agarose degradation exhibit potential in the fields of bioenergy, medicine, and cosmetics. Mangrove sediments (MGSs) provide a special environment to enrich enzymes for agarose degradation. However, representative investigations of the agarlytic genes in MGSs have been rarely reported. In this study, agarlytic genes in MGSs were researched in detail from the aspects of diversity, abundance, activity, and location through deep metagenomics sequencing. Functional genes in MGSs were usually incomplete but were shown as results, which could cause virtually high number of results in previous studies because multiple fragmented sequences could originate from the same genes. In our work, only complete and nonredundant (CNR) genes were analyzed to avoid virtually high amount of the results. The number of CNR agarlytic genes in our datasets was significantly higher than that in the datasets of previous studies. Twenty-one recombinant agarases with agarose-degrading activity were detected using heterologous expression based on numerous complete open-reading frames, which are rarely obtained in metagenomics sequencing of samples with complex microbial communities, such as MGSs. Aga2, which had the highest crude enzyme activity among the 21 recombinant agarases, was further purified and subjected to enzymatic characterization. With its high agarose-degrading activity, resistance to temperature changes and chemical agents, Aga2 could be a suitable option for industrial production. The agarase ratio with signal peptides to that without signal peptides in our MGS datasets was lower than that of other reported agarases. Six draft genomes, namely, Clusters 1–6, were recovered from the datasets.The taxonomic annotation of these genomes revealed that Clusters 1, 3, 5, and 6 were annotated as Desulfuromonas sp., Treponema sp., Ignavibacteriales spp., and Polyangiaceae spp., respectively. Meanwhile, Clusters 2 and 4 were potential new species. All these genomes were first reported and found to have abilities of degrading various important polysaccharides. The metabolic pathway of agarose in Cluster 4 was also speculated. Our results showed the capacity and activity of agarases in the MGS microbiome, and MGSs exert potential as a repertory for mining not only agarlytic genes but also almost all genes of the carbohydrate–active enzyme family.